Reconceptualizing Islamic Financial Markets: A Moral-Economic Equilibrium Approach: Merekonseptualisasi Pasar Keuangan Islam: Pendekatan Keseimbangan Moral-Ekonomi - Anton Budiyono; Ayus Ahmad Yusuf (jsd: Journal of Society and Development, 2026)
Recurring global financial crises and widening distributive inequalities expose the systemic failures of the conventional market efficiency paradigm in ensuring economic stability and justice. This article aims to reconceptualize financial markets through a moral-economic equilibrium approach as an alternative to the mainstream model. Employing a qualitative method via a critical literature review of conventional and Islamic economics, the study deconstructs the underlying assumptions of both systems to produce a new theoretical reconstruction. Research findings indicate that Islamic financial markets function as equilibrium systems that simultaneously integrate economic efficiency, moral values, and social objectives. The core foundation lies in the prohibition of Riba, Gharar, and Maysir, integrated with risk-sharing mechanisms and organic linkages to the real sector. This moral-economic equilibrium demonstrates that market efficiency and distributive justice can harmoniously synergize within the Maqashid al-shariah framework. In conclusion, the article asserts that Islamic financial markets represent a value-based financial paradigm oriented toward socio-economic welfare and sustainable development. The primary theoretical contribution is the provision of a new analytical framework that synthesizes moral and economic dimensions into a single, cohesive equilibrium construct to address the limitations of the efficiency paradigm in responding to contemporary global economic stability challenges.